An efficient algorithm for Volt/Var control at distribution systems including DER - Niknam, Taher (Journal of intelligent & fuzzy systems, 2009)
Distributed energy resource (DER) systems are small-scale power generation technologies used to provide an alternative to or an enhancement of the traditional electric power system. These generators are usually connected to distribution networks. This paper presents a new price based methodology to daily Volt/Var control in distribution systems including DERs. DERs have much impact on the daily Volt/Var control according to the small X/R ratio and radial configuration of distribution systems. Due to private ownership of DERs, a price-based compensation methodology is proposed as a proper signal to encourage owners of DERs in active and reactive power generation. Since daily Volt/Var control is a mixed integer nonlinear programming problem, an evolutionary algorithm based on Ant Colony Optimization (ACO) is used to determine the active and reactive power values of DERs, reactive power values of capacitors and tap positions of transformers for the next day. The results indicate that the proposed encouraging factor has improved the performance of distribution networks on a large scale.